Problems of Development of Social Business - Abbasov, A.; Abbasov, S. (Економічний вісник Донбасу, 2021)
The article reveals corporate social responsibility, business socialization, the essence, meaning and criteria of social business. Appropriate generalizations were made on the various scientific and theoretical views of economists on the assessment of corporate social responsibility. The characteristics, basic principles and philosophy of social business are explained in detail. The philosophy of social business is based on the fact that the investor is not given dividends on profits received from entrepreneurial activity, he receives only the amount of money invested, and the rest of the investment is invested in business development and the implementation of socially significant projects. The features of the formation of family farms (family business) as an important form of social entrepreneurship and development prospects at the regional level are revealed. Family business is a social business model in which family members participate in management and succession in family traditions. Famous family business firms have evolved and become large companies influencing the global economy. In the Republic of Azerbaijan, ABAD (Simplified Support to Family Business) provides support to family enterprises in the field of arts and crafts, as well as business planning, marketing, design, finance, accounting and legal assistance. Certification of manufactured products according to the “one-stop shop” principle, organization of logistics and sales is carried out by ABAD. Suggestions were made to increase the role of social business in improving the welfare of the population and in the sustainable development of the national economy. У статті розкрито корпоративну соціальну відповідальність, соціалізацію бізнесу, сутність, значення та критерії соціального підприємництва. Зроблено відповідні узагальнення щодо різноманітних науково-теоретичних поглядів економістів на оцінку соціальної відповідальності підприємств. Детально пояснюється характеристика, основні принципи та філософія соціального підприємництва. Філософія соціального підприємництва ґрунтується на тому, що інвестору не виплачуються дивіденди на прибуток, який отримано від підприємницької діяльності, – він отримує лише суму вкладених грошей, а решта інвестицій вкладається у розвиток бізнесу та реалізацію соціально значущих проєктів. Розкрито особливості формування сімейного господарства (сімейного бізнесу) як важливої форми соціального підприємництва та перспективи розвитку на регіональному рівні. Сімейний бізнес – це соціальна бізнес-модель, у якій члени сім’ї беруть участь в управлінні та спадкоємності у сімейних традиціях. Фірми сімейного бізнесу розвивалися і стали великими компаніями, що впливають на світову економіку. В Азербайджанській Республіці ABAD (спрощена підтримка сімейного бізнесу) надає підтримку сімейним підприємствам у сфері мистецтва та ремесел, а також у бізнес-плануванні, маркетингу, дизайні, фінансах, бухгалтерській та юридичній допомозі. Крім цього, підтримка здійснюється і при сертифікації виробленої продукції відповідно до принципу «єдиного вікна», організації логістики та збуту. Розроблено практичні рекомендації щодо посилення ролі соціального підприємництва у підвищенні добробуту населення та сталому розвитку національної економіки. В статье раскрыты корпоративная социальная ответственность, социализация бизнеса, сущность, значение и критерии социального предпринимательства. Сделаны соответствующие обобщения различных научно-теоретических взглядов экономистов на оценку социальной ответственности предприятий. Детально разъясняется черта, главные принципы и философия социального предпринимательства. Философия социального предпринимательства основывается на том, что инвестору не выплачиваются дивиденды на прибыль, полученную от предпринимательской деятельности, - он получает только сумму вложенных денег, а остальные инвестиции вкладываются в развитие бизнеса и реализацию социально значимых проектов. Раскрыты особенности формирования семейного хозяйства (семейного бизнеса) как важной формы социального предпринимательства и перспектив развития на региональном уровне. Семейный бизнес – это социальная бизнес-модель, в которой члены семьи принимают участие в управлении и преемственности в семейных традициях. Фирмы семейного бизнеса развивались и стали крупными компаниями, влияющими на мировую экономику. В Азербайджанской Республике ABAD (упрощенная поддержка семейного бизнеса) оказывает поддержку семейным предприятиям в сфере искусства и ремесел, а также в бизнес-планировании, маркетинге, дизайне, финансах, бухгалтерской и юридической помощи. Кроме того, поддержка осуществляется и при сертификации производимой продукции в соответствии с принципом «единого окна», организации логистики и сбыта. Разработаны практические рекомендации по усилению роли социального предпринимательства в повышении благосостояния населения и устойчивом развитии национальной экономики.